The Pedagogical Study in Character Development to Increase The Moral Awareness of Students in Schools - Dessy Selinda Bayurini; Sofyan Sauri; Eviana Hikamudin (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2024)
Character education is important and needs to be strengthened constantly in light of the rising rate of juvenile and community violence. The purpose of this research is to determine the internal elements that affect students' moral awareness and to create learning strategies for character development that can raise students' moral awareness in the classroom. Qualitative research using descriptive methods was conducted at SMA Negeri 1 Ciampel and SMA Negeri 2 Klari. The findings of the study indicate that the reasons behind students' lack of morality are their own choices, such as those who continue to break the rules. In an attempt to combat this, the instructor, pupils, and parents have come to a consensus